Enhancing the oxidation resistance of Nb-Si based alloys by yttrium addition. (October 2018) - Guo, Yueling; Jia, Lina; Zhang, Huarui; Zhang, Fengxiang; Zhang, Hu
Abstract: The effect of yttrium on the microstructure and high-temperature oxidation performance of Nb-15Si-24Ti-4Cr-2Al-2Hf (at.%) alloys was investigated. Alloys containing different yttrium contents were designed, aiming at maximizing the beneficial effect of yttrium addition and avoiding the possible adverse effect of over-doped yttrium. Results showed that Y was primarily partitioned in γ-Nb5 Si3, relative to Nb solid solution (Nbss), Nb3 Si and α-Nb5 Si3 . Microstructural refinement and oxidation resistance enhancement were achieved by yttrium addition up to 0.3 at.%, accompanied by the transition towards parabolic oxidation kinetics. An adverse effect of over-doped yttrium (0.5 at.% addition) by coarsening the microstructure and deteriorating the oxidation resistance was confirmed. A relatively continuous glassy SiO2 layer was generated in the oxide scale formed on the Y-containing alloys with enhanced oxidation resistance. Highlights: Microstructures of Nb-Si based alloys are refined by Y addition (<0.3 at.%). Oxidation resistance of Nb-Si alloys is improved by Y addition (<0.3 at.%). Excessive addition of Y damages the oxidation resistance.